2009
DOI: 10.1093/jnci/djp180
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Hepatitis B Virus Mutations and the Risk of Hepatocellular Carcinoma: A Meta-Analysis

Abstract: BackgroundThe association between hepatitis B virus (HBV) mutations and hepatocarcinogenesis remains controversial because of conflicting data in the literature. We conducted a meta-analysis of case–control and cohort studies to examine HBV PreS, enhancer II (EnhII), basal core promoter (BCP), and precore mutations in relation to the risk of hepatocellular carcinoma (HCC).MethodsWe searched databases for studies of these associations that were published in English or Chinese up to August 31, 2008. HBV mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
316
2
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(343 citation statements)
references
References 62 publications
19
316
2
6
Order By: Relevance
“…Independent factors associated with HCC included age, abnormal ALT, HBV DNA ≥ 4 log10 copies per ml, genotype C, and core promoter mutations: C1653T, T1674C / G, T1753V, and A1762T / G1764A (TA). Apart from the T1674C / G mutation, these fi ndings are in agreement with previous studies ( 16 ). A previous meta-analysis found that the frequency of C1653T, T1753V, and TA mutations increased successively from ASC to cirrhosis ( 16 ).…”
Section: Conflict Of Interestsupporting
confidence: 92%
See 2 more Smart Citations
“…Independent factors associated with HCC included age, abnormal ALT, HBV DNA ≥ 4 log10 copies per ml, genotype C, and core promoter mutations: C1653T, T1674C / G, T1753V, and A1762T / G1764A (TA). Apart from the T1674C / G mutation, these fi ndings are in agreement with previous studies ( 16 ). A previous meta-analysis found that the frequency of C1653T, T1753V, and TA mutations increased successively from ASC to cirrhosis ( 16 ).…”
Section: Conflict Of Interestsupporting
confidence: 92%
“…Apart from the T1674C / G mutation, these fi ndings are in agreement with previous studies ( 16 ). A previous meta-analysis found that the frequency of C1653T, T1753V, and TA mutations increased successively from ASC to cirrhosis ( 16 ). Th is study confi rmed that even aft er adjustment for age (and duration of chronic HBV infection), core promoter mutations are associated with HCC.…”
Section: Conflict Of Interestsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the results have been inconsistent. Up to now, there has been only one published meta-analysis article focusing on the C1653T mutation,and the conclusion is that C1653T is associated with an increased risk of HCC (Liu et al, 2009). With much more studies focusing on the correlation of C1653T mutation with HCC,we update the meta-analysis and product a subgroup analysis to give a more comprehensive understanding on C1653T mutation with HCC risk.…”
Section: Research Articlementioning
confidence: 99%
“…As mutações comumente relatadas associadas ao CHC são mutações na região pré-S/S (pré-S1 e pré-S2) e várias mutações na região pré-core/core: dupla mutação no promotor do core A1762T/G1764A, G1896A, T1753V (A, C ou G) e C1653T (82)(83)(84)(85)(86) …”
Section: Mutações No Genoma Do Hbv E Hepatocarcinogêneseunclassified